Tantangan Perkawinan Beda Negara: Suatu Kajian Komparatif Hukum Indonesia dan Hukum Perdata Internasional - Norayanti, Norayanti Simaremare; Pristika Handayani , Pristika Handayani; Dwi Afni Maileni, Dwi Afni Maileni (Universitas Semarang, 2025)
This study aims to examine the legal challenges of cross-national marriages through a comparative analysis between Indonesian Law and Private International Law. The background of this research is the increasing phenomenon of cross-border marriages as a consequence of globalization, which not only involves cultural and nationality differences but also raises legal issues related to validity, recognition, and legal consequences. The urgency of this research lies in the disharmony of regulations and differences in legal systems that often create both administrative and substantive obstacles, thereby affecting legal certainty and the protection of the rights of husbands, wives, and children. The research method employed is normative juridical with a descriptive-analytical approach by reviewing legislation, legal doctrines, and principles of Private International Law. The findings indicate that Indonesia’s Marriage Law remains limited in accommodating the complexity of cross-national marriages, particularly concerning registration, citizenship status of children, joint property, divorce, and inheritance rights. The novelty of this research lies in its comparative approach that links Indonesian legal norms with the principles of Private International Law, providing a more comprehensive understanding of regulatory disharmony. In conclusion, without legal harmonization, cross-national couples will continue to face uncertainty; therefore, this study recommends reforming the Marriage Law to be more adaptive to global realities, strengthening administrative mechanisms for marriage registration, and enhancing regulatory dissemination to ensure legal certainty, rights protection, and justice for the parties involved. Penelitian ini bertujuan mengkaji tantangan hukum dalam perkawinan beda negara melalui analisis komparatif antara Hukum Indonesia dan Hukum Perdata Internasional (HPI). Latar belakang penelitian didasari oleh meningkatnya fenomena perkawinan lintas negara akibat globalisasi yang tidak hanya memunculkan perbedaan budaya dan kewarganegaraan, tetapi juga menimbulkan persoalan hukum terkait keabsahan, pengakuan, serta akibat hukumnya. Urgensi penelitian ini terletak pada disharmoni regulasi dan perbedaan sistem hukum yang kerap menimbulkan hambatan administratif maupun substantif, sehingga berdampak pada kepastian hukum dan perlindungan hak suami, istri, maupun anak. Metode yang digunakan adalah yuridis normatif dengan pendekatan deskriptif-analitis melalui kajian peraturan perundang-undangan, doktrin hukum, serta prinsip-prinsip HPI. Hasil penelitian menunjukkan bahwa Undang-Undang Perkawinan di Indonesia masih terbatas dalam mengakomodasi kompleksitas perkawinan lintas negara, khususnya terkait pencatatan, status kewarganegaraan anak, harta bersama, perceraian, dan hak waris. Kebaruan penelitian ini terletak pada penggunaan pendekatan komparatif yang menghubungkan norma hukum Indonesia dengan prinsip HPI, sehingga menghasilkan gambaran yang lebih komprehensif mengenai titik-titik disharmoni regulasi. Kesimpulannya, tanpa harmonisasi hukum, pasangan lintas negara akan terus menghadapi ketidakpastian hukum; oleh karena itu, penelitian ini merekomendasikan reformasi UU Perkawinan yang lebih adaptif terhadap realitas global, penguatan mekanisme administrasi pencatatan, serta peningkatan sosialisasi regulasi untuk menjamin kepastian hukum, perlindungan hak, dan keadilan bagi para pihak.